Clinical-pathogenetical role of dynamics of concentration of interleukin-6 depending on polymorphism of its gene in conducting antiviral therapy in patients with chronic hepatitis C - Kalashnyk, K; Riabokon, Yu; Riabokon, O; Калашник, К. В.; Рябоконь, Ю. Ю.; Рябоконь, Е. В.; Калашнік, Кирило Вадимович; Рябоконь, Юрій Юрійович; Рябоконь, Олена Вячеславівна (My University, 2018)
To determine the role of the dynamics of the content of IL-6 depending on the polymorphism of the gene that it encodes in achieving a stable virological response in the antiviral treatment of patients with chronic hepatitis C.
Клинико-патогенетическая роль динамики содержания интерлейкина-6 в зависимости от полиморфизма его гена при проведении противовирусной терапии больным хроническим гепатитом С